An inside-look into Lysinibacillus sphaericus toxicity: marker genes and prophages (2017)
The very effective and widely used entomopathogenic bacterium Lysinibacillus sphaericus is recognized as a highly heterogeneous group since the early 1990s. It has been proposed by many authors that it comprises more than one species, but insufficient research has limited the discovery of discriminatory phenotypic traits, preventing clarification. Recent genomic-wide studies have further confirmed the monophyletic grouping of L. sphaericus toxic strains, suggesting the need for the definition of a new species. Mtx mosquitocidal toxins along with Bin proteins have been determined to be a distinctive feature of this lineage, but additional molecular features that could distinguish between toxic and non-toxic strains remains undiscovered. Furthermore, 16S phylogenies have failed to exclusively cluster all toxic strains in a single clade, highlighting the need for a marker gene capable of accurate reconstruction of the genome-wide phylogeny. In this study, 5 marker genes were identified using a fragmented all-to-all genome comparison. Four of them reconstructed the genomic phylogeny with 80% accuracy, with a toxic single clade. Finally, evidence for prophage relationship with toxicity was found and the S-layer candidate marker gene was present in a prophage region on all toxic strains